(untitled) (Research, Society and Development, 2021)
Periodontal disease is a chronic inflammatory disease caused by colonization of pathogens that affects the tissues that support and support the teeth. The contribution of periodontitis to the occurrence of ischemic stroke can be indirectly related through inflammatory mechanisms. The aim of this study was to verify the prevalence of periodontal changes in patients affected by ischemic stroke. This is a cross-sectional, observational study in which periodontal disease was evaluated by means of periodontal probing and the diagnosis of periodontal disease in 20 volunteers who joined the Fundação de Beneficência Hospital de Cirurgia in 2020. As a result we have that of the evaluated 10 were female, with an average age of 68.2 (± 10.2). Of these, 95% had a stroke less than 1 year ago, 60% was the first history of the disease, 90% were hypertensive and 60% diabetic, 95% did not take hyperplasic drugs, 45% had the first degree of study and 70% had been to the dentist for over 1 year. Regarding periodontal disease, 80% were diagnosed with generalized periodontal disease, 35% in stage IV and 65% in grade B. It was concluded that periodontal disease proved to be prevalent among those evaluated, which may be characteristic of processes associated with stroke.